Regulatory Pathways For Smart Grid Development in China - Brunekreeft, Gert; Luhmann, Till; Menz, Tobias; Müller, Sven-Uwe; Recknagel, Paul (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2015)
A series of reforms have greatly improved the efficiency, reliability, and environmental performance of the Chinese power sector. However, significant challenges remain: rapidly rising electricity demand, concerns about power system reliability and energy security, environmental degradation and climate change. China’s government explicitly set up the goal of accelerating the development of so-called smart grids which might help to overcome the challenges mentioned above.  Yet, considerable difficulties exist in adjusting the regulatory environment of China’s electric power system to enable an effective and efficient development of smart grids in China. Based on a detailed analysis of the Chinese and the German power system and regulatory environment as well as international experience, seven recommendations to promote smart grid development in China have been developed. The recommendations relate to a broad range of regulatory topics. In order to give an impression of how policy goal prioritization influences the timeline in which the recommendations should be implemented, the study outlines possible regulatory pathways for three specific energy policy goals. These roadmaps are intended to serve as blueprints for policy makers, who have to decide about proper regulation based on the individual Chinese prioritization of energy policy.    The content: ·         Detailed overviews of the existing electric power system, the envisaged development of smart grids, and the regulatory environment in China and Germany ·         Recommended approaches for smart grid development in China ·         Regulatory pathways for smart grid development in China    Editors: ►           Prof. Dr. Gert BRUNEKREEFT, Jacobs University Bremen gGmbH ►           Dr. Till LUHMANN, BTC Business Technology Consulting AG ►           Dr. Tobias MENZ, BTC Business Technology Consulting AG ►           Dr. Sven-Uwe MÜLLER, Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH ►           Paul RECKNAGEL, Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH.